PENGUATAN KELOMPOK TANI MELALUI OPTIMALISASI DAN SINERGI LINGKUNGAN SOSIAL - Sri Subekti; Sudarko Sudarko; Sofia Sofia (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
The purpose of this research is to analyze the process of strengthening farmer groups through the optimization of environmental and social synergy in farmer groups. The results showed the strengthening of farmer groups can be grown by increasing the synergistic relationship between farmer groups with the social environment. Social environment that can support the strengthening of farmer groups are farmers, gapoktan, Department of Agricultural, Research Institute, Laboratory of pests and diseases, PPAH, financial institutions, HIPPA, traders, kiosk production facilities and universities.Keywords: farmer groups, social environmental, synergy